2016
DOI: 10.1186/s11671-015-1223-6
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Doped (La,Sr)MnO3 Manganites as Promising Mediators of Self-Controlled Magnetic Nanohyperthermia

Abstract: Fe-doped La0.77Sr0.23Mn1 − yFeyO3 nanoparticles have been synthesized by sol-gel method, and ceramic samples based on them were sintered at 1613 K. Crystallographic and magnetic properties of obtained nanoparticles and ceramic samples have been studied. It has been established that cell volume for nanoparticles increases with growing of iron content, while this dependence displays an opposite trend in the case of ceramic samples. Mössbauer investigations have shown that in all samples, the oxidation state of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…According to XRD investigations, all samples are single-phase and crystallize in the distorted perovskite structure. The average nanoparticle sizes lie in the range 25-35 nm for the Fe-substituted series [17] and 31-38 nm for the Sm-substituted one [18].…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…According to XRD investigations, all samples are single-phase and crystallize in the distorted perovskite structure. The average nanoparticle sizes lie in the range 25-35 nm for the Fe-substituted series [17] and 31-38 nm for the Sm-substituted one [18].…”
Section: Resultsmentioning
confidence: 98%
“…Magnetic properties of the samples of both series were reported in Refs. [17,18]. It was shown that both kinds of substitutions (Mn → Fe and La → Sm) give rise to the decrease of room-temperature magnetization and the Curie temperature T C .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their Curie temperature strongly depends on the chemical composition: it demonstrates the maximal value at y  ≈ 0.3 ( T C max  ≈ 370 K) and quite sharply decreases as y deviates from 0.3. Earlier, it was shown that fine controlling of the Curie point within the narrow temperature range can be reached by low-level substitutions in manganese sublattice [22]. At the same time, partial substitutions of La 3+ ions by other rare-earth ions (for instance, by Nd 3+ ) may be one more possible way of fine-tuning the phase-transition temperature, since magnetic interactions in manganites are sensitive to the lattice parameters and strength of local lattice distortions [23].…”
Section: Introductionmentioning
confidence: 99%